2007
DOI: 10.5367/000000007781236871
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Doctoral Students as Brokers between Industry and Academia

Abstract: The authors look at the learning context for 23 industrial doctoral students and assess the prerequisites for the development of their identity as researchers. The students are located in three different industrial research schools – Management, Medical Bioinformatics and Building and Indoor Climate. The purpose of the study is to describe the students' total learning environment and to ascertain what factors influence, hinder or encourage their development within the doctoral education process. To ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Comparing the findings of these studies with the ones above, one can see that whilst students during the PhD do not have significantly different career ambitions, research on doctoral holders careers indicates that they have different career trajectories. On the other hand, it is also possible that students who choose to collaborate during the doctoral degree have particular motivations and characteristics that make them both inclined to collaboration and later private sector employment, and that it has relatively little to do with the PhD experience itself (Gemme and Gringas 2004;Wallgren and Dahlgren 2007). Such individual characteristics could be age, gender, family background, prior employment and particularly private sector employment prior to entering the PhD program.…”
Section: Doctoral Students On the University-industry Interface-lessomentioning
confidence: 96%
See 1 more Smart Citation
“…Comparing the findings of these studies with the ones above, one can see that whilst students during the PhD do not have significantly different career ambitions, research on doctoral holders careers indicates that they have different career trajectories. On the other hand, it is also possible that students who choose to collaborate during the doctoral degree have particular motivations and characteristics that make them both inclined to collaboration and later private sector employment, and that it has relatively little to do with the PhD experience itself (Gemme and Gringas 2004;Wallgren and Dahlgren 2007). Such individual characteristics could be age, gender, family background, prior employment and particularly private sector employment prior to entering the PhD program.…”
Section: Doctoral Students On the University-industry Interface-lessomentioning
confidence: 96%
“…Wallgren and Dahlgren's (2005) qualitative study of Swedish PhD students in industrial research schools indicate that the type of firm involved in the collaborations (R&D intensive firm, engineering firm and consultancy firm) have an impact on how collaborations are carried out, and how supportive the firms are as research environments for doctoral students. Wallgren and Dahlgren's (2007) paper point to organizational practices and routines in different collaborative arrangements, which influences the learning experience of the students. Butcher and Jeffrey (2007) emphasize that how supervision and communication is handled in collaborative projects, has an impact on how successful the collaboration is perceived by the students.…”
Section: Characteristics Of Doctoral Student-firm Interactionsmentioning
confidence: 99%
“…The inability to discuss their research with fellow students can then force the student outside the 'circle of socialization that takes place' in a typical university setting (Slaughter et al 2002, 299). This isolation was confirmed in a study of industry supervision in Sweden, where either (1) both the academic and industry supervisors were too busy to provide regular supervision, or (2) the industry partner demonstrated 'little interest' in the student's research (Wallgren and Dahlgren 2007). So too, supervisors, who trained as academics, may be unfamiliar with the demands of industry and unable to prepare students to cope with the tensions between the values and goals of universities and industry (Manathunga, Lant, and Mellick 2007;Pearson and Brew 2002).…”
Section: Assessment and Evaluation In Higher Educationmentioning
confidence: 91%
“…Previous studies have demonstrated that experiences, which affect academic identity, are often multi-dimensional, including: experiences of learning, research and publication; interaction with supervisor and peers; and perceived overall learning environment (Wallgren & Dahlgren, 2007). Positive training experience helps to enhance students' professional skills and to acculturalize them into an academic lifestyle.…”
Section: Micro-level Views On Experience and Career Capacitiesmentioning
confidence: 99%